Pendidikan dan Promosi Kesehatan Tentang Masalah Hipertensi dan Pola Hidup Bersih Sehat Pada Masyarakat - Triningtias, Nur (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of public health promotion is to initiate good habits and behaviors so that public health can improve as early as possible. This study aims to determine the public response to health promotion and education around hypertension and a clean and healthy lifestyle. The technique used is the literature review methodology. Several previous studies have used other methodologies. Presentation materials about hypertension and its risk factors, such as power point files, LCDs, and projector screens, are some of the tools used in health promotion initiatives to avoid hypertension. Blood pressure checks and counseling are usually the first steps in the health promotion process to adopt a clean and healthy lifestyle (PHBS), which is then followed by conversations and question and answer sessions. With this, the researcher concludes that health education and promotion in the community are continuously needed. Many people are not yet aware of the need to carry out health education and socialization, on an ongoing basis, so this is not only done by educational institutions. Moreover, education and promotion about the problem of hypertension and a clean and healthy lifestyle in the community is an obligation of all parties and cross-sectoral, which is not only the community as an object. However, the community is also the subject of the importance of health so that it is continuously maintained periodically.